Anisotropic fracture mechanics of pre-cracked T4,4,4-Graphyne Nanosheets: Effects of crack geometry and temperature - Chuanyuan Tan; Ali Ghasemi (PLoS ONE, 2026)
An atomistic study is conducted to elucidate the fracture behavior of pristine and centrally pre-cracked T 4,4,4 -graphyne nanosheets (150 Å × 150 Å) under uniaxial tension in both X- and Y-directions. Stress–strain responses are analyzed as functions of crack length (30–60 Å), orientation (0°–90°), and temperature (200–1000 K). Elastic modulus degradation is captured by power-law and trigonometric models, yielding high correlation coefficients. Ultimate tensile strength and fracture strain are shown to decline with increasing crack length and temperature, while toughness and mode I fracture toughness illustrate anisotropic energy absorption and crack-tip shielding effects, particularly under X-loading where ligament bridging and bond rotation mechanisms are activated. Thermal softening is modeled via the Wachtman equation, revealing near-linear modulus reduction and an inversion of directional stiffness at elevated temperatures. The results demonstrate that crack-length thresholds (~30% of sheet width) and mixed-mode loading conditions critically govern the transition from ductile-like to brittle fracture regimes in anisotropic 2D graphyne nanosheets.